Revisiting discourse on Islam and state relation in Indonesia: the view of Soekarno, Natsir and Nurcholish Madjid - Ahmad Ali Nurdin (Indonesian Journal of Islam and Muslim Societies, 2016)
This paper focuses on debates between Soekarno, Natsir and Nurcholish Madjid to whether Indonesian state should be based on Islam ideologically or not. Soekarno, was in favor of the separation between Islam and state and against the idea of a formal-legal relationship between them. In Soekarno’s belief, by separating religion from the state, it does not mean that Islamic teachings are automatically marginalized. Natsir argued against Soekarno’s idea that Islam should be separated from the state. Natsir believed that Islam is a way of life in which it not only guides Muslim peoples on ritual matter but also on worldly matters including how to manage a state. Madjid seems to propose the middle path between Soekarno and Natsir in his struggle to ‘Islamize’ Indonesia. On the one hand, Madjid opposes the idea of making Indonesia an Islamic state, and on the other hand, Madjid also refuses that Indonesian become totally a secular state. Madjid tried to develop a new format for political Islam in which substance, rather than form, serves as his primary orientations. Kajian ini berfokus pada perdebatan antara Soekarno, Natsir dan Nurcholish Madjid tentang apakah negara Indonesia harus didasarkan pada Islam ideologis atau tidak. Soekarno adalah pendukung pemisahan antara Islam dan negara dan menentang gagasan hubungan formal-legal antara keduanya. Dalam keyakinan Soekarno, dengan memisahkan agama dari negara, itu tidak berarti bahwa ajaran Islam secara otomatis terpinggirkan. Natsir menentang gagasan Soekarno bahwa Islam harus dipisahkan dari negara. Natsir percaya bahwa Islam adalah cara hidup yang tidak hanya membimbing masyarakat Muslim tentang masalah ritual tetapi juga pada hal-hal duniawi termasuk bagaimana mengelola negara. Madjid tampaknya mengusulkan jalan tengah antara Soekarno dan Natsir dalam perjuangan untuk ‘mengislamkan’ Indonesia. Di satu sisi, Madjid menentang ide menciptakan Indonesia sebagai negara Islam, dan di sisi lain, Madjid juga menolak bahwa Indonesia menjadi benar-benar sebuah negara sekuler. Madjid mencoba untuk mengembangkan format baru bagi Islam politik di mana substansi, bukan bentuk, berfungsi sebagai orientasi utamanya.